Project Based Learning Model in Islamic Education Learning to Increase Students' Interest in Learning at SMP Negeri 3 Lubuk Sikaping - Gustana, Wedi Andi (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student interest in Islamic religious education learning using the project based learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the project based learning model can improve student interest in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 59.78%, the first cycle 62.87% and in the second cycle it increased to 70.12%. Thus, the use of project based learning model can be used as an alternative to improve student interest in Islamic religious education learning.